The Initial Step Towards Establishing a Quantitative, Magnetic Resonance Imaging-Based Framework for Response Assessment of Spinal Metastases After Stereotactic Body Radiation Therapy. Issue 5 (14th August 2021) - Jabehdar Maralani, Pejman; Tseng, Chia-Lin; Baharjoo, Hamidreza; Wong, Erin; Kapadia, Anish; Dasgupta, Archya; Howard, Peter; Chan, Aimee K M; Atenafu, Eshetu G; Lu, Hua; Tyrrell, Pascal; Das, Sunit; et al.
Abstract: BACKGROUND: There are no established threshold values regarding the degree of growth on imaging when assessing response of spinal metastases treated with stereotactic body radiation therapy (SBRT). OBJECTIVE: To determine a magnetic resonance imaging-based minimum detectable difference (MDD) in gross tumor volume (GTV) and its association with 1-yr radiation site-specific (RSS) progression-free survival (PFS). METHODS: GTVs at baseline and first 2 post-SBRT scans (Post1 and Post2, respectively) for 142 spinal segments were contoured, and percentage volume change between scans calculated. One-year RSS PFS was acquired from medical records. The MDD was determined. The MDD was compared against optimal thresholds of GTV changes associated with 1-yr RSS PFS using Youden's J index, and receiver operating characteristic curves between timepoints compared to determine which timeframe had the best association. RESULTS: A total of 17 of the 142 segments demonstrated progression. The MDD was 10.9%. Baseline-Post2 demonstrated the best performance (area under the curve [AUC] 0.90). Only Baseline-Post2 had an optimal threshold > MDD at 14.7%. Due to large distribution of GTVs, volumes were split into tertiles. Small tumors (GTV < 2 cc) had optimal thresholds of 42.0%, 71.3%, and 37.2% at Baseline-Post1 (AUC 0.81), Baseline-Post2 (AUC 0.89), and Post1-Post2 (AUC 0.77), respectively. Medium tumors (2 ≤ GTV ≤ 8.3 cc) all demonstrated optimal thresholds < MDD, with AUCs ranging from 0.65 to 0.84. Large tumors (GTV > 8.3 cc) had 2 timepoints where optimal thresholds > MDD: Baseline-Post2 (13.3%; AUC 0.97) and Post1-Post2 (11.8%; AUC 0.66). Baseline-Post2 had the best association with RSS PFS for all tertiles. CONCLUSION: Given a MDD of 10.9%, for small GTVs, larger (>37%) changes were required before local failure could be determined, compared to 11% to 13% for medium/large tumors.